Pengaruh Lingkungan Kerja Serta Keselamatan dan Kesehatan Kerja terhadap Kineja Karyawan PT Tunas Baru Lampung Tbk Palembang - Elsa Elsa; Roswaty Roswaty; Muhammad Bahrul Ulum (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study was to find out the effect of the Work Environment and Occupational Health and Safety on the work Performance Employees of PT Tunas Baru Lampung Tbk Palembang. This type of research is descriptive quantitative by distributing questionnaires through the Google Form, observations, and documents. Sample of the present study was filled with 124 respondents. The Sources of information for this study are secondary data and primary data using purposive sampling method. Based on the t-test resuts, it shows that work environment has a positive and significant effect on employee performance in PT Tunas Baru Lampung Tbk Palembang with a significant value of 0.000 <0.05 and tcount > ttable (2.472 > 1.9797), thus rejecting H0,, H1 is accepted. Occupational Health and safety has positive and significant jmpact on the employee’s performance in PT Tunas Baru Lampung Tbk Palembang with a significant value of 0.000 <0.05 and t-count > ttable (4.562 > 1.9797) then H0 is rejected H1 is accepted. Then score F test analysis (simultaneous) show that the Work Environment and Occupational Health and Safety positive and important impact the Performance of employees of PT Tunas Baru Lampung Tbk Palembang. With a significant value of 0.000 <0.05 and the Fcount value is greater than Ftable (49,311 > 0.392). It cauld be said that the higher the Work Environment and Occupational Health and Safety the better the Performance of the staff. The results of the determination is (R2) 0.449. it shows the effet of the environment and work safety and health variabel on Employee Performance while (44.9%) this value shows that the worker Performance variabel can be explained by Work Environment And work Health while and the remaining 55.1% by other variables that not included in this study.